Powder metallurgical processing of Al matrix composite reinforced with AlSiCrMnFeNiCu high-entropy alloys: Microstructure, thermal stability, and microhardness - Shadangi Y.; Chattopadhyay K.; Mukhopadhyay N.K. (My University, 2025)
The present work deals with powder metallurgical processing of AA 6082 Al matrix composite reinforced with non-equiatomic AlSiCrMnFeNiCu high-entropy alloy (HEA). The structure, microstructure, morphology, and phase composition of these Al-HEA nanocomposite powders were discerned through XRD and TEM, SEM–EDS, respectively. The AlSiCrMnFeNiCu HEA used as reinforcement was found to have a two-phase microstructure with a major and minor fraction corresponding to the B2-type (a = 0.29 nm; cP2) and Cr5Si3-type (a = b = 0.9165 nm, c = 0.4638 nm; tI32) phases, respectively. Mechanical milling (MM) imparts significant refinement, and nanostructuring of grains (~ 10–12 nm) for Al-HEA for nanocomposite powder was observed. These powders of Al-HEA was found to be thermally stable up to 650 ℃. Further, these Al-HEA nanocomposite powders were consolidated through pressure-less sintering at 560 ℃, which led to the formation of a thin ~ 400–500 nm transitional layer at the interface. The microhardness of these Al-HEA composites were tuned in the range of ~ 0.90 to 1.81 GPa. Graphical abstract: [Figure not available: see fulltext.] © 2023, The Author(s).